Diversified health insurance contributions in terms of medical condition and change of health behaviors - survey of select office workers group from Lublin region - Ewelina Kozłowska; Anna Kowalczyk (Kazimierz Wielki University, 2017)
Introduction. Health care is an important element of the policy of every State. Health in addition to the fact that is a value and measure to achieve better quality of life is also a resource for society, ensuring its social and economic development. Therefore, it is important to strive for development of such health care system, which will carry out health expectations and needs of citizens. Polish health insurance system is based on the principle of social solidarity, which guarantees equal access to healthcare services. The contribution shall be calculated in proportion to the amount of earnings of the insured person, regardless of health status or individual risk factors. Aim. Getting to know the opinion of selected group of professionally active persons on the impact of diversified health insurance contributions in terms of medical condition (the poorer medical condition all the higher contributions) and change of health behaviors. Material and method. The study was conducted in the period of III-V 2014 among 937 office workers using diagnostic survey. The author's questionnaire form constituted the research tool. Collected material was subjected to statistical analysis using nonparametric χ2 Pearson statistical test. Results. Implementation of changes in calculation of health contribution would induce 67% of respondents for more frequent use of preventive tests. More than half of surveyed (59%) declared that would be able to change the way of feeding on healthier. It would also induce respondents for more frequent physical activity in different forms (57%). Almost half of surveyed (53%) answered that implementation of new calculation of contributions to the health insurance would motivate to give up smoking. Conclusions. Diversified health insurance contributions in terms of medical condition would result among majority of respondents in resignation from unhealthy behaviors. The financial factor more often motivates men than women and persons with greater attention to their own health. The change of calculating contribution would affect the increase in frequency of using preventive examinations.